(untitled) (Research, Society and Development, 2023)
Myocardial revascularization is one of the most performed procedures for the correction of ischemia caused by obstruction of the coronary arteries. The severity of the condition of patients who undergo coronary artery bypass grafting has increased considerably in recent years. The objective of this study is to describe the care provided by the Nursing team to patients undergoing Myocardial Revascularization in a Coronary Care Unit in Belém-Pará. The data of this scientific research were collected through an interview, with a semi-structured questionnaire, with 10 nurses working in a cardiology referral hospital in the city of Belém in the state of Pará for the year 2021, in the coronary sector unit. This study is framed as a descriptive and qualitative research. It can be shown that the planning of the systematization of nursing care for patients undergoing myocardial revascularization describes and identifies the care provided by the nursing team to this patient profile.